Tārīkh-i Shāh Ṣafī : Tārīkh-i taḥawwulāt-i Īrān dar sālhā-yi 1038-1052 HQ, bih inḍimām-i Mabādi-yi tārīkh-i zamān-i Nawwāb Riḍwān Makān (Shāh Ṣafī), Tārīkh-i taḥawwulāt-i Īrān dar sālhā-yi 1038-1041 HQ - Tafrishī, Abu ʼl-Mafākhir (Miras Maktoob, ISBN: 9789004365452., 2019)
During the reign of Shāh ʿAbbās I (r. 996-1038/1587-1629), the Safavid state was at the top of its power and magnificence. When ʿAbbās died in 1038/1629, he was succeeded by his grandson Sam Mīrzā, son of former crown-prince Muḥammad Bāqir Mīrzā who had been murdered on his father's orders in Rasht in 1024/1615, taking on the name of Shāh Ṣafī. The reign of Shāh Ṣafī (r. 1038-52/1629-42) marks the beginning of a steady decline of the Safavid empire, ending with the deposition of its last ruler, Shāh ʿAbbās III, by Nādir Khān in 1148/1736. The present work by Abu ʼl-Mafākhir Tafrishī is a history of the reign of Shāh Ṣafī. Often based on the author's personal experience or on other eyewitness accounts, it is a welcome source of information on the reign of this cruel and incapable Safavid emperor. In the appendix: a short text on the reign of Shāh Ṣafī by the author's brother, Muḥammad Ḥusayn Tafrishī.